2015
DOI: 10.1371/journal.ppat.1005346
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomic Profiling Reveals Epstein-Barr Virus Protein Kinase Integration of DNA Damage Response and Mitotic Signaling

Abstract: Epstein-Barr virus (EBV) is etiologically linked to infectious mononucleosis and several human cancers. EBV encodes a conserved protein kinase BGLF4 that plays a key role in the viral life cycle. To provide new insight into the host proteins regulated by BGLF4, we utilized stable isotope labeling by amino acids in cell culture (SILAC)-based quantitative proteomics to compare site-specific phosphorylation in BGLF4-expressing Akata B cells. Our analysis revealed BGLF4-mediated hyperphosphorylation of 3,046 uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 121 publications
(145 reference statements)
1
59
1
1
Order By: Relevance
“…However, these studies relied on in vitro assays, and consequently, the substrates identified might not be representative of the true substrates during viral replication. Recently, the same group published data obtained from phosphoproteomic profiling of BGLF4-expressing cells (55). Such experiments would be invaluable in delineating the substrates of KSHV ORF36, as well as other herpesviral kinases.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies relied on in vitro assays, and consequently, the substrates identified might not be representative of the true substrates during viral replication. Recently, the same group published data obtained from phosphoproteomic profiling of BGLF4-expressing cells (55). Such experiments would be invaluable in delineating the substrates of KSHV ORF36, as well as other herpesviral kinases.…”
Section: Discussionmentioning
confidence: 99%
“…The Akata-BX1 (EBV + ) and Akata-4E3 (EBV -) cells were grown in RPMI 1640 media supplemented with 10% fetal bovine serum (FBS) (Gibco) in 5% CO 2 at 37°C (Li et al, 2011(Li et al, , 2012b (Li et al, 2015). Cells were cultured for at least six doubling times for complete incorporation.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…23227; Pierce). Peptides were prepared by an in-solution tryptic digestion protocol (Li et al, 2015). Trypsin digestion efficiency was assessed by SDS-PAGE and Coomassie Brilliant Blue staining before further processing.…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations